Comparative study of the cytologic diagnosis, specimen adequacy, sensitivity, and cost effectiveness of liquid-based cytology with that of conventional PAP tests - M. S., Manickadevi; Hemalatha, S. V.; M., Thangamani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer is the most common cancer among women in many developing countries constituting 20-30% of female cancers. In the developed western countries, it accounts for only 4-6% of female cancers. This difference largely reflects the impact of mass screening using cervical cytologic methods. Methods: Prospective observational study.300 patients were selected from the gynaecology OPD of Government RSRM lying In Hospital. A detailed history was taken and they were informed about the screening procedures and counselling given regarding the necessity for their participation in screening program. Both conventional pap and liquid-based cytology were performed in the same patient and results were analyzed. Results: Out of 300 patients screened for cancer cervix with conventional Pap and liquid-based cytology in the same patient, LBC detection rate of cervical abnormalities and HSIL was higher than that of CP. False -ve rate of LBC was only 2%. Sensitivity is 97% and false positive rate is 44%. The sensitivity is equal to that of the gold standard method. Infection detection rate increased with LBC. Specimen adequacy improved with LBC substantially. The collection sample device brush was found superior to the wooden Ayre’s spatula in both not injuring tissues and specimen collection. The adverse impact on a woman's quality of life caused by unnecessary repeat smears and possible investigations would reduce the cost with LBC. The economic evidence suggests that LBC screening every 3 years or longer may be cost-effective. LBC reduced the pressure on a skilled workforce. Conclusions: As stated in WHO press release, dated 11 October 2001 it can be concluded through the current study that we should aim to divert our resources to screening and treating the high-risk groups of women. The effort once or twice in their lifetime will reduce the incidence of cervical cancer by 50%.